Handbook of Oral Anticoagulation - Lip, Gregory YH.; Shantsila, Eduard; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
This book covers a wide range of disorders such as atrial fibrillation, artificial heart valves, deep vein thrombosis, pulmonary embolism and stroke. Handbook of Oral Anticoagulation aims to provide an accessible overview of the exciting new developments in this field. Incorporating numerous quick-reference tables and figures and fully referenced throughout to key papers and the latest reviews, it will be a useful resource for all healthcare professionals involved in thromboprophylaxis.
The coagulation pathway and approaches to anticoagulation -- Common clinical indications for anticoagulation -- Vitamin K antagonists and their limitations -- Hemorrhage risks, patient perspectives, and quality-of-life issues -- New oral anticoagulants -- Future directions.
Keywords: Medicine; Family medicine; Cardiology; Hematology; Emergency medicine; Medicine & Public Health; Cardiology; Hematology; General Practice / Family Medicine; Primary Care Medicine; Pharmacotherapy